Harnessing CRISPR potential for intervertebral disc regeneration strategies - Milheiro, Catarina; Moura, Maria L.; Amendola, Mario; Barbosa, Mário A.; Caldeira, Joana (Frontiers in Bioengineering and Biotechnology, 2025)
Genome editing technologies, particularly CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats), have broadened the possibilities of genetic research and molecular biology by enabling precise modifications of the genome, offering novel therapeutic potential for various disorders. Herein, we present an overview of traditional genome editing techniques and delve deeper into the CRISPR toolbox, with particular attention given to epigenetic and transcriptional regulation. In the context of the intervertebral disc (IVD), CRISPR offers an unprecedented approach to address the mechanisms underlying tissue degeneration, advancing the development of revolutionary therapies for Low Back Pain (LBP). As so, we showcase how to leverage CRISPR systems for IVD. This cutting-edge technology has been successfully used to improve our understanding of IVD biology through functional studies and disease modeling. Most relevant research prioritizes new targets associated with the extracellular matrix (ECM), pain sensing or inflammatory pathways. Promising CRISPR applications encompass IVD regeneration by recapitulation of a regenerative environment or by targeting important degenerative catalysts. In the future, priority should be given to fetal gene reactivation, multiple healthy gene expression enhancement and disease-associated polymorphisms’ correction. Despite several challenges such as effective delivery, off-target effects, as well as ethical and safety concerns, exciting clinical trials are anticipated in the years to come, providing more effective and long-lasting solutions for IVD degeneration.